The seed of the Amazonian fruit Couepia bracteosa exhibits higher scavenging capacity against ROS and RNS than its shell and pulp extracts. Issue 9 (2nd September 2015) - Berto, Alessandra; Ribeiro, Alessandra Braga; Sentandreu, Enrique; de Souza, Nilson Evelázio; Mercadante, Adriana Zerlotti; Chisté, Renan Campos; Fernandes, Eduarda
<x xml:space="preserve">Abstract</x> Couepia bracteosa is an interesting source of bioactive compounds which may be investigated for protecting human health against oxidative damage.